ACADEMIC FREEDOM ATTRACTIVE CHALLENGE OF MODERN UNIVERSITY - G.O. Abisheva; A. Sh. Nurgalieva; D.T. Ismailova; N.T. Ismailova; A.K. Zhumagulova (Academic Journal of Physical and Chemical Sciences, 2019)
This article discusses the basic principles of academic mobility in the framework of the Bologna process. The process of implementing academic mobility has been studied: social - the free movement of students, undergraduates, PhD doctoral students, academic staff, the interchange of teaching and research technologies, and the second - the organization of joint educational programs: tools of academic mobility in order to obtain educational and professional competencies in higher education institutions of the world educational space for one to two semesters. This will increase the competitiveness of education and the development of human capital by providing affordable quality education for the stable development of the economy in order to achieve the highest level of education in higher education institutions that will satisfy the needs of the modern market.